Cyber-crime during the COVID-19 pandemic - Adil Radoini (Freedom from Fear, 2020)
The pandemic of COVID-19 and the imposed lockdown, has led to more people to be confined at home with many more hours to spend online each day and increasingly relying on the Internet to access services, they normally obtain offline.